Application of Primer LEP in Detecting Pork Adulteration in Meat Burger Using Hot-Start Real-Time Polymerase Chain Reaction Combined with Melting Curve Analysis - Tjondro, Fortunella; ., Sismindari (Fakultas Farmasi, Universitas Gadjah Mada, 2014)
The development of pig species detection in food is increasing due to pork adulteration. Hitherto, the strongest method to detect and quantify pig presence in food is Real-Time Polymerase Chain Reaction. The object of this study is to know whether published primers that amplified leptin gene (LEP primer) could be used to detect and quantify pig’s presence in meat burger using Real-Time Polymerase Chain Reaction with dye intercalator- based detection. Genomic DNA isolation was done by proteinase K digestion. Porcine DNA was amplified using LEP primer with Hot-Start Real-Time Polymerase Chain Reaction combined with Melting Curve Analysis. Condition of Real-Time PCR used in this experiment could amplify not only 152bp porcine leptin gene fragment with Tm value of 83.5oC but also 205bp cow’s leptin gene fragment with Tm 80oC. The result suggests that LEP primer is not a species-specific primer so it can’t be used to quantify pig’s presence in meat burger using Real-Time Polymerase Chain Reaction with dye intercalator-based detection.